Short-Circuit Performance Analysis of Commercial 1.7 kV SiC MOSFETs Under Varying Electrical Stress - Shahid Makhdoom; Na Ren; Ce Wang; Yiding Wu; Hongyi Xu; Jiakun Wang; Kuang Sheng (Micromachines)
The short-circuit (SC) robustness of SiC MOSFETs is critical for high-power applications, yet 1.2 kV devices often struggle to meet the industry-standard SC withstand time (SCWT) under practical operating conditions. Despite growing interest in higher voltage classes, no prior study has systematically evaluated the SC performance of 1.7 kV SiC MOSFETs. This study provides the first comprehensive evaluation of commercially available 1.7 kV SiC MOSFETs, analyzing their SC performance under varying electrical stress conditions. Results indicate a clear trade-off between SC withstand time (SCWT) and drain-source voltage (VDS), with SCWT decreasing from 32 µs at 400 V to 4 µs at 1100 V. Under 600 V, a condition representative of practical use cases in many high-voltage applications, the devices achieved an SCWT of 12 µs, exceeding the industry-standard 10 µs benchmark—a threshold often unmet by 1.2 kV devices under similar conditions. Failure analysis revealed gate dielectric breakdown as the dominant failure mode at VDS ≤ 600 V, while thermal runaway was observed at higher voltages (VDS = 800 V and 1100 V). These findings underscore the critical importance of robust gate drive designs and effective thermal management. By surpassing the shortcomings of lower voltage classes, 1.7 kV SiC MOSFETs can be a more reliable, and efficient choice for operating at higher voltages in next-generation power systems.